Polarization analysis of THz radiation using a wire grid polarizer and ZnTe crystal - F. A. Zainullin; D. I. Khusyainov; M. V. Kozintseva; A. M. Buryakov (Российский технологический журнал, 2022)
Objectives. Terahertz time domain spectroscopy (THz-TDS) is currently a promising research method in pharmacology and medicine due to the high sensitivity of terahertz radiation to the chemical composition and molecular structure of organic compounds. However, due to the chirality of many biomolecules, their analysis is performed by THz irradiation with circular dichroism. In particular, circular dichroism of THz radiation allows the study of “soft” vibrational movements of biomolecules with different chiralities. Therefore, when studying such biological materials, accurate control of THz radiation parameters is essential. The paper describes a method for characterizing THz radiation polarization on the example of a black phosphorus source material.Methods. The analysis of polarization parameters of THz radiation experimentally obtained by THz-TDS and using terahertz polarizers was performed by mathematical modeling of the interaction between THz radiation and a ZnTe crystal as a detector.Results. Two schemes of terahertz spectroscopy with the ZnTe crystal as the detector were discussed in detail. The polarization parameters were determined using one or two wire-grid THz polarizers. An expression for approximating the dependences of the peak-to-peak amplitude of THz radiation on the rotation angle of the wire-grid THz polarizer for these cases was derived. The impact of the terahertz electric field intensity value on the shape of polarization dependences was considered. The rotation angle of the polarization ellipse of THz radiation emitted by the surface of a bulk-layered black phosphorus crystal illuminated by femtosecond laser pulses was determined.Conclusions. The amplitude of the THz radiation electric field intensity begins to impact the shape of polarization dependences when its value becomes comparable to or exceeds 40 kV/cm.